Dataset – Personalization of Politics Expert Survey (PoPES) (1985-2016) - Marino, Bruno; Martocchia Diodati, Nicola; Verzichelli, Luca (2023)
This dataset provides data on different dimensions of personalization of politics in Western Europe from 1985 until 2016 thanks to data collected via an expert survey. Data are available for a series of countries and more than 110 parties. The dataset includes data on four dimensions of personalization. One dimension (country-level) is related to the impact of personalization in general elections. Three further dimensions (party-level) are related to: the autonomy of the party leader in selecting candidates for general elections; the autonomy of the party leader in defining the policy-making agenda of the party; the control of the party organization by the party leader. The unit of analysis is, for the country-level dimension, the country in the general election while, for the party-level dimensions, the unit of analysis is the political party in the general election. This dataset provides data on different dimensions of personalization of politics in Western Europe from 1985 until 2016 thanks to data collected via an expert survey. Data are available for a series of countries and more than 110 parties. The dataset includes data on four dimensions of personalization. One dimension (country-level) is related to the impact of personalization in general elections. Three further dimensions (party-level) are related to: the autonomy of the party leader in selecting candidates for general elections; the autonomy of the party leader in defining the policy-making agenda of the party; the control of the party organization by the party leader. The unit of analysis is, for the country-level dimension, the country in the general election while, for the party-level dimensions, the unit of analysis is the political party in the general election.